2009
DOI: 10.1083/jcb.200806185
|View full text |Cite
|
Sign up to set email alerts
|

Actin filament dynamics are dominated by rapid growth and severing activity in the Arabidopsis cortical array

Abstract: Metazoan cells harness the power of actin dynamics to create cytoskeletal arrays that stimulate protrusions and drive intracellular organelle movements. In plant cells, the actin cytoskeleton is understood to participate in cell elongation; however, a detailed description and molecular mechanism(s) underpinning filament nucleation, growth, and turnover are lacking. Here, we use variable-angle epifluorescence microscopy (VAEM) to examine the organization and dynamics of the cortical cytoskeleton in growing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
366
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(391 citation statements)
references
References 62 publications
24
366
1
Order By: Relevance
“…Inhibition of growing/shrinking cycles of tubules after F-actin has depolymerized is supported by the large number of blind ended tubules in Figures 2 and 3, which may have started a cycle but not completed it. We further postulate that there is a polarity for ER tubule remodeling and the actomyosin system (Figure 8, processes 1 to 3 and 5); growth is mainly driven by actin polymerization, as supported by the observation that the rate of in vivo actin polymerization (1.7 mm/s; Staiger et al, 2009) is very close to the rate of tubule growth previously reported (1.34 6 0.54 mm/s; Sparkes et al, 2009b), while shrinkage is mediated by (+) end-directed myosin processivity. Myosins are classically defined as (+) end-directed motors.…”
Section: Er Tubule Growth/shrinkagementioning
confidence: 95%
“…Inhibition of growing/shrinking cycles of tubules after F-actin has depolymerized is supported by the large number of blind ended tubules in Figures 2 and 3, which may have started a cycle but not completed it. We further postulate that there is a polarity for ER tubule remodeling and the actomyosin system (Figure 8, processes 1 to 3 and 5); growth is mainly driven by actin polymerization, as supported by the observation that the rate of in vivo actin polymerization (1.7 mm/s; Staiger et al, 2009) is very close to the rate of tubule growth previously reported (1.34 6 0.54 mm/s; Sparkes et al, 2009b), while shrinkage is mediated by (+) end-directed myosin processivity. Myosins are classically defined as (+) end-directed motors.…”
Section: Er Tubule Growth/shrinkagementioning
confidence: 95%
“…The meshwork is approximately 100 nm thick, has a pore size of about 50 nm and attaches to the plasma membrane via ezrin, moesin and class I myosins [15][16][17] . Actin polymerization at the plasma membrane is constantly balanced by actin destruction at the cytosolic side of the cortex by actin severing proteins, cofilin and destrin 14,18,19 , and by the debranching activity of coronins 20 . The cortical cytoskeleton is thus highly dynamic, turning over in under a minute 18 .…”
Section: [H1] Structure Of the Cortical Cytoskeletonmentioning
confidence: 99%
“…Pharmacological studies show that alterations to the equilibrium between F-actin and monomeric actin inhibit the expansion of pollen tubes and root hairs (Gibbon et al, 1999;Miller et al, 1999;Vidali et al, 2001), demonstrating that a fine balance of actin assembly and disassembly is required for tip growth. More recently, time-lapse imaging of the cortical actin cytoskeleton in planta provides further support for rapid remodeling of the actin cytoskeleton (Era et al, 2009;Staiger et al, 2009;Vidali et al, 2009a;Smertenko et al, 2010). Individual actin filaments undergo stochastic dynamics whereby rapid elongation of filaments is interspersed by severing events (Michelot et al, 2007;Staiger et al, 2009) that result in the dramatic reorganization of the actin cytoskeleton on the order of seconds.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, time-lapse imaging of the cortical actin cytoskeleton in planta provides further support for rapid remodeling of the actin cytoskeleton (Era et al, 2009;Staiger et al, 2009;Vidali et al, 2009a;Smertenko et al, 2010). Individual actin filaments undergo stochastic dynamics whereby rapid elongation of filaments is interspersed by severing events (Michelot et al, 2007;Staiger et al, 2009) that result in the dramatic reorganization of the actin cytoskeleton on the order of seconds.…”
Section: Introductionmentioning
confidence: 99%